Jes Peter Caspersen: Sådan var det. E- rindringsbilleder. Sønderjyske Levnedsløb nr. 27. (Historisk Samfund for Sønderjylland, 1990). 310 s. - Becker-Christensen, Henrik (Historie/Jyske Samlinger, 1993)
-